Regio‐ and Stereoselective Synthesis of (Z)‐3‐Ylidenephthalides via H3PMo12O40‐Catalyzed Cyclization of 2‐Acylbenzoic Acids with Benzylic Alcohols. Issue 11 (8th September 2021) - Yang, Guoping; Li, Ke; Lin, Xiaoling; Li, Yijin; Cui, Chengxing; Li, Shixiong; Cheng, Yuanyuan; Liu, Yufeng
Main observation and conclusion: We report an exclusively tandem C—O and C—C bond forming beyond the esterification and cyclization reaction of 2‐acylbenzoic acids with alcohols to regio‐ and stereoselective synthesis of the ( Z )‐3‐ylidenephthalides. The reaction uses the nontoxic, inexpensive H3 PMo12 O40 as catalyst and produces water as the sole by‐product, making the reaction environmentally benign and sustainable. Moreover, this reaction features an eco‐friendly reaction condition, facile scalability, and easy derivatization of the products to drugs and bioactive compounds. The mechanism studies and density functional theory calculations reveal that the appropriate acid catalyst is the key to the selectivity of this transformation. Abstract : A regio‐ and stereoselective synthesis of ( Z )‐3‐ylidenephthalides via H3 PMo12 O40 ‐catalyzed cyclization of 2‐acylbenzoic acids with benzylic alcohols was developed.